Remarques sur une famille caravanière à Palmyre - Yon, Jean-Baptiste (1998)
The city of Palmyra, in the Syrian steppe, is well known for its caravan-trade, which made its fortune during the Roman period. The Aramaic and Greek epigraphical evidence allows a precise picture to be drawn of the way members of the city's upper classes were in command of the trade. Among them, the family of Marcus Ulpius Iarhai is in a conspicuous position in the middle of the 2nd cent. From the particular example of this individual, the study focuses on the trade and its organization. The vocabulary used in the inscription shows that all commercial expeditions were not ' 'caravans' ' and that the different positions (synodiarches, traders of higher or lower status) were clearly defined.